LEGAL PROBLEMS OF EURASION ECONOMIC UNION ESTABLISHMENT - Ibragimov Жамаладен Ибрагимович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
This article considers legal foundations of Eurasion Economic Union creation on the basis of Commonwealth of Independent States (CIS), Eurasion Economic Commonwealth, Custs Union, Common Economic Space. The foundation of future Eurasian Economic Union is in these different forms of cooperation, which will become top of the integration on the post-Soviet space.